Thermal insulation systems for road bases with foam glass gravel - Semenov Vyacheslav (Magazine of Civil Engineering, 2022)
The article discusses the systems of roadbed construction on permafrost and heaving soils with foam glass gravel backfill. The aim of the research was to substantiate the expediency of using foam glass gravel in roadway insulation systems on problematic, including heaving and permafrost soils. This goal was achieved by determining the properties of foam glass gravel, as well as calculating the thermal characteristics and temperature fields in the roadbed. The strength of foam glass gravel, depending on its degree of compaction (from 10 to 50 %), is in the range of 0.90...1.58 MPa, and the thermal conductivity coefficient is from 0.087 to 0.099 W/(m°C). It was found that the water absorption of gravel by volume does not exceed 1.8 %, and the sorption humidity does not exceed 4.2 %. The novelty of the work lies in a comprehensive study of insulation systems using domestically produced foam glass gravel using digital imitation of heat transfer and modeling of the formation of temperature fields. It has been established that the use of heat-insulating backfill of foam glass gravel with a thickness of 0.25 m allows to protect the permafrost soil of the road base from thawing, and to limit the freezing depth to 0.2 m, versus 2.6 m without heat-insulating layer – in case of protection of the road base from freezing. The significance of the research is the development of constructive solutions for the use of foam glass gravel in roadway insulation systems, arranged on problem soils in permafrost conditions and on soils with frost heaving.